The application of industrialised building system in residential project - Syazana, Abdul Aziz (2010)
Industrialised Building System (IBS) is an alternative of construction that can change many aspects in building construction. The Industrialised Building System (IBS) is a construction system that is built using prefabricated components and is systematically done using machine, formworks and other forms of mechanical equipment. Before this, the construction industry in Malaysia had faced so many problems related to the increasing of using foreign workers, waste of building materials, uncontrolled quality of building materials, unsafe construction site and delay of construction period. This study is done in order to identify the number of Industrialised Building System (IBS) used in residential project, to analyze the types of Industrialised Building System (IBS) used in residential project, and to analyze the method to expand the use of Industrialised Building System (IBS) in residential project. The study is done by distributing the questionnaire by postage delivery and conducting an interview. Through detailed reading and distributed questionnaire, the number of Industrialised Building System used in residential project is identified. To conclude, the Industrialised Building System is still not widely used in the residential project. Most of the housing companies are using precast-concrete framing, panel and box system in residential project. Based on the results obtained, to reduce the Industrialised Building System (IBS) component price rate is the most preferable solution to this matter.